Pengaruh Fenomena "Marriage is Scary" terhadap Stigma Pernikahan dan Perilaku Seksual Pra-Nikah pada Generasi Muda - Millatul Azizah; Nofita Nur Aini; Sekar Sari; Moh Amirul Hamzah (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2025)
This study aims to explore the influence of the “Marriage is Scary” phenomenon on the views of marriage among the younger generation. This study used an experimental approach with quantitative methods. Data collection techniques included questionnaires from individuals aged 12-30 years old as well as content analysis and comments on social media. The results showed that 83.2% of the younger generation were affected by the “Marriage is Scary” content, especially in terms of emotional and financial uncertainty. This stigma is often related to the fear of losing independence, financial worries, and domestic violence. However, this phenomenon did not result in an increase in pre-marital sexual behavior, with young people still choosing committed relationships. This research shows that access to positive information and sexual education is crucial to changing negative views of marriage. In addition, good sexual education also needs to be supported by broader approaches, such as understanding mental health, communication in relationships, and social expectation management, to help overcome the negative stigma associated with marriage among young people.